Ying-Shih Yü, Trade and Expansion in Han China. A Study in the Structure of Sino-Barbarian Economic Relations. University of California Press, Berkeley y Los Angeles, 1967. 251 pp. - Ana Lía Payró (El Colegio de México, A.C., 1971)
-